Inverse screening of Simvastatin kinase targets from glioblastoma druggable kinome. (June 2020) - Li, Yi; Wei, Xu; Wang, Qiuhong; Li, Wei; Yang, Tao
Graphical abstract: Highlights: An inverse screening protocol is described to discover unexpected kinase targets from glioblastoma druggable kinome. The binding behavior of Simvastatin to the kinome is profiled systematically via an integrative computational approach. Simvastatin shows low affinity to the well-established GBM target of PI3K/Akt/mTOR pathway. EGFR T790 M gatekeeper mutation can reduce Simvastatin sensitivity by changing the ligand binding mode. Abstract: The statin drug Simvastatin is a HMG-CoA reductase inhibitor that has been widely used to lower blood lipid. However, the drug is clinically observed to reposition a significant suppressing potency on glioblastoma (GBM) by unexpectedly targeting diverse kinase pathways involved in GBM tumorigensis. Here, an inverse screening strategy is described to discover potential kinase targets of Simvastatin. Various human protein kinases implicated in GBM are enriched to define a druggable kinome; the binding behavior of Simvastatin to the kinome is profiled systematically via an integrative computational approach, from which most kinases have only low or moderate binding potency to Simvastatin, while only few are identified as promising kinase hits. It is revealed that Simvastatin can potentially interact with certain known targets or key regulators of GBM such as ErbB, c-Src and FGFR signaling pathways, but exhibit low affinity to the well-established GBM target of PI3K/Akt/mTOR pathway. Further assays determine that Simvastatin can inhibit kinase hits EGFR, MET, SRC and HER2 at nanomolar level, which are comparable with those of cognate kinase inhibitors. Structural analyses reveal that the sophisticated T790 M gatekeeper mutation can considerably reduce Simvastatin sensitivity to EGFR by inducing the ligand change between different binding modes.